Dry sliding wear performance of nanostructured WC–12Co deposited through microwave cladding. (November 2015) - Zafar, Sunny; Sharma, Apurbba Kumar
Abstract: In the present work, two WC–12Co powders with particle size in the micrometric and nanometric range were used to develop clads on austenitic stainless steel using microwave hybrid heating technique. The microstructure of the micrometric clads exhibited skeleton structured carbides distributed in the metallic matrix, while uniformly distributed clusters of nanocarbides were observed in the nanometric clad. The average microhardness of the nanometric and the micrometric clad layer was observed to be 1564±53 HV and 1138±90 HV, respectively. The nanometric clads exhibited approximately 54% higher wear resistance. This is attributed to the uniform distribution and higher volume fraction of the nanocarbides present in the clad. Graphical abstract: Highlights: Sliding wear performance of nanometric WC–12Co microwave clad was investigated. The presence of nanocarbides ensued increased carbide volume fraction in the clads. Uniformly distributed nanocarbides enhanced the hardness of the nanometric clads. Nanometric clads were superior is dry sliding than the micrometric clads.